IDENTIFYING CAREER SELECTION OF HIGH SCHOOL STUDENTS BASED ON JOHN HOLLAND'S THEORY - Ramahwati, Novia Tri; Sri Ramadhani, Helfa; Ayunda Restu, Intan (Jurnal Kopendik, 2023)
Career selection for students is a very important aspect to be able to develop a career in the future, career selection itself requires maturity in taking a certain career, strategies in career selection for students can be done with career guidance and career planning, career guidance is usually carried out by BK teachers at school who aim to be able to understand the characteristics of themselves in terms of talent, interests, values and characteristics personality so that it can determine career choices for the next level As for John Holland's theory in this career selection Mentions that to choose a career learners will be assessed in two or three personality types that stand out in him and then will match the type of each learner with the potential that exists in him The method carried out in this writing is literature review thus career selection for learners based on John Holland's theory is by adjusting the students' self-characteristics or interests and talents so that later the careers chosen by students are in accordance with their passions and environment so that students can run the careers they have with a satisfying feeling because they are in accordance with their characteristics.